Vesiculation of biological membrane driven by curvature induced frustrations in membrane orientational ordering - Jesenek D (Dove Medical Press, 2013)
Dalija Jesenek,1 Šarká Perutková,2 Wojciech Góźdź,3 Veronika Kralj-Iglič,4 Aleš Iglič,2,5 Samo Kralj1,61Condensed Matter Physics Department, Jožef Stefan Institute, Ljubljana, Slovenia; 2Laboratory of Biophysics, Faculty of Electrical Engineering, University of Ljubljana, Ljubljana, Slovenia; 3Department of Complex Systems and Chemical Processing of Information, Institute of Physical Chemistry, Polish Academy of Sciences, Warsaw, Poland; 4Laboratory of Clinical Biophysics, Faculty of Health Studies, University of Ljubljana, Ljubljana, Slovenia; 5Laboratory of Clinical Biophysics, Faculty of Medicine, University of Ljubljana, Ljubljana, Slovenia; 6Department of Physics, Faculty of Natural Sciences and Mathematics, University of Maribor, Maribor, SloveniaAbstract: Membrane budding often leads to the formation and release of microvesicles. The latter might play an important role in long distance cell-to-cell communication, owing to their ability to move with body fluids. Several mechanisms exist which might trigger the pinching off of globular buds from the parent membrane (vesiculation). In this paper, we consider the theoretical impacts of topological defects (frustrations) on this process in the membranes that exhibit global in-plane orientational order. A Landau–de Gennes theoretical approach is used in terms of tensor orientational order parameters. The impact of membrane shapes on position and the number of defects is analyzed. In studied cases, only defects with winding numbers m = ±1/2 appear, where we refer to the number of defects with m = 1/2 as defects, and with m = –1/2 as anti-defects. It is demonstrated that defects are attracted to regions with maximal positive Gaussian curvature, K. On the contrary, anti-defects are attracted to membrane regions exhibiting minimal negative values of K. We show on membrane structures exhibiting spherical topology that the coexistence of regions with K > 0 and K < 0 might trigger formation of defect–anti-defect pairs for strong enough local membrane curvatures. Critical conditions for triggering pairs are determined in several demonstrative cases. Then the additionally appeared anti-defects are assembled at the membrane neck, where K < 0. Consequent strong local fluctuations of membrane constituent anisotropic molecules might trigger membrane fission neck rupture, enabling a membrane fission process and the release of membrane daughter microvesicles (ie, vesiculation).Keywords: structural transitions, topological defects, membrane microvesicles, membrane curvature, membrane fission, vesiculation